An investigation into China’s online catering food safety governance efficacy based on the strategies of frequent supervision and strict penalty - Shen, Cong; Wei, Mingxia; Li, Chaoyang; Hao, Xin; Wang, Lin (Frontiers in Sustainable Food Systems, 2024)
Introduction Enhancing the efficacy of online food safety supervision requires thoughtful selection and efficient application of regulatory measures. Methods This study examined the current state of online food safety supervision in the important food producing city in central China of Zhengzhou. The effectiveness of supervision frequency and penalty on food safety governance of online catering was examined through model construction based on the optimal law enforcement theory. The efficacy of monitoring was evaluated using real supervision and punishment data from the online catering sector in a Chinese new first-tier city. Results and discussion Results showed that although high-frequency and high-penalty supervision are two common methods of online food safety governance, the deterrent effect of high-frequency supervision on online food businesses is more significant for improving the supervision efficiency of the online catering market. Simultaneously, bolstering the education of caterers and food operators as well as raising their degree of training are also efficient ways to raise the efficacy of government oversight. The application of law enforcement economics is broadened in this study, which also has implication for the advancement of credit rating and classification supervision in the area of food safety for online catering.